2003
DOI: 10.1172/jci200317100
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in a CD44 variant of inflammatory cells enhances the mitogenic interaction of FGF with its receptor

Abstract: Synovial fluid cells from joints of rheumatoid arthritis (RA) patients express a novel variant of CD44 (designated CD44vRA), encoding an extra trinucleotide (CAG) transcribed from intronic sequences flanking a variant exon. The CD44vRA mutant was detected in 23 out of 30 RA patients. CD44-negative Namalwa cells transfected with CD44vRA cDNA or with CD44v3-v10 (CD44vRA wild type) cDNA bound FGF-2 to an equal extent via their associated heparan sulfate chains. However, Namalwa cells, immobilizing FGF-2 via their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…We previously showed that the CD44v3ev10 transcript of synovial fluid cells from the joints of RA patients (designated CD44vRA) contains an extra trinucleotide, CAG, which is not included in the corresponding wild type molecule, CD44v3e v10, predominantly expressed on primary keratinocytes [12]. We now describe the generation of mAbs exclusively recognizing CD44vRA and inducing apoptosis in synovial fluid cells from RA patients, but not in their PBLs.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…We previously showed that the CD44v3ev10 transcript of synovial fluid cells from the joints of RA patients (designated CD44vRA) contains an extra trinucleotide, CAG, which is not included in the corresponding wild type molecule, CD44v3e v10, predominantly expressed on primary keratinocytes [12]. We now describe the generation of mAbs exclusively recognizing CD44vRA and inducing apoptosis in synovial fluid cells from RA patients, but not in their PBLs.…”
Section: Discussionmentioning
confidence: 86%
“…Does expression of cell surface CD44vRA entail a functional meaning with physiological or pathological consequences? Namalwa cells and RA synovial fluid cells expressing CD44vRA and immobilizing FGF-2 activate FGF-receptor bearing cells more intensively than corresponding cells expressing the wild type CD44v3ev10 [12]. As activation of the FGF-receptor on fibroblasts and endothelial cells in inflammatory joints of RA patients is an important factor in the pathology of the disease [20e22], it is conceivable that CD44vRA expression contributes to the RA inflammatory process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell surface CD44 can be present as either the standard isoform or as variant isoforms in a cell-specific manner (2,32). The structural diversity of CD44 isoforms correlates with a diverse array of overlapping yet distinct functions in cell adhesion, migration, and proliferation (10,18,23). Alternations in CD44 expression have been documented in tissue inflammation, wound healing, and tumor metastasis (16) (5,8,37,39).…”
mentioning
confidence: 99%